Relatório para o Governo da Província de Cabo Delgado e Agência Espanhola de Cooperação Internacional para o Desenvolvimento (AECID) - Umarji, Mariam; Makda, Sadya; Paulo, Arsénio; Lalá, Aly (SAL & Caldeira, 2009)
O relatório que se segue retrata a avaliação conduzida ao Sistema de Gestão de Finanças Públicas da Província de Cabo Delgado considerando o ciclo orçamental do ano de 2008, considerando a informação de contabilidade, reporte e auditoria relacionada com este ano mas produzida em 2007 e em 2009. A avaliação teve como base a Metodologia PEFA – Despesa Pública e Responsabilidade Financeira – devidamente adaptada ao nível subnacional (província) de acordo com as orientações metodológicas emanadas pelo Secretariado PEFA. Foram utilizados um total de 25 indicadores para a avaliação. Os indicadores reflectem a situação actual do sistema e fornecem um ponto de comparação para avaliações ou seguimentos futuros dos progressos esperados nos processos de planificação, orçamentação, contabilidade, reporte e auditoria da província. Esta Avaliação Sumária apresenta as constatações finais da equipa de consultores sendo fruto do trabalho de campo realizado para inquérito e recolha de evidência combinada com a revisão documental de informação recebida e disponibilizada de forma a se poder realizar a avaliação dos diferentes indicadores.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; budget / orçamento; fiscal policy / política fiscal

Relatório Final da Pesquisa sobre o Impacto da Descentralização dos Fundos Sectoriais de Estradas, Águas e de Construção Acelerada de Salas de Aulas nas Províncias, nos Distritos e nas Autarquias Locais - Kulipossa, Fidelx Pius; Nguenha, Eduardo Jossias (The Open University consultancy, 2009)
A 17a Sessão Ordinária do Conselho de Ministros realizada em 2007 tomou a corajosa decisão de descentralizar os fundos dos sectores de estradas, águas, agricultura, e infra-estruturas de educação e saúde para garantir a implementação efectiva da Lei 8/2003 sobre os Órgãos Locais do Estado e materializar os objectivos estratégicos definidos no PARPA II e no Plano Quinquenal do Governo. Tal decisão, em parte, reconhece que a pobreza absoluta que flagela muitos cidadãos está estreitamente ligada à falta de acesso aos serviços básicos tais estradas, água potável, infra-estruturas escolares e de saúde e outros serviços úteis para a sobrevivência e sustentabilidade da vida humana. Com efeito, presumia-se que ao se descentralizar estes fundos sectoriais para os níveis provinciais e distritais, as instituições locais teriam maior capacidade de resposta às demandas da população em termos de prestação de melhores serviços, de maneira que ela estivesse mais satisfeita e participasse activamente na vida política e económica do país. Em termos de produção legislativa, regista-se avanço significativo na descentralização de fundos sectoriais. Porém, sendo essa legislação muito recente e em fase primária de sua implementação, constatam-se algumas reservas na implementação efectiva da mesma. Por exemplo, os progressos sectoriais na descentralização de fundos são diferenciados. No sector de estradas, os fundos são geridas e os pagamentos efectuados a partir do nível central através da Administração Nacional de Estradas (ANE). Relativamente aos sectores de água e de educação (construção acelerada de salas de aulas) os fundos são geridos a nível provincial e os pagamentos feitos nos dois níveis: provincial e distrital. A leitura do processo, e com respeito às constatações feitas nas províncias de Nampula e Gaza, onde decorreu o trabalho de campo, revelou diferenças peculiares nos avanços e na forma de abordagem da descentralização nas duas províncias, particularmente nos aspectos referentes a critérios de planificação, definição de prioridades, alocação de recursos e fluxos financeiros. As diferenças verificadas para as duas províncias, que podem ser explicadas, em parte, pela diferença de maturidade na condução dos processos de descentralização entre Nampula e Gaza, sendo a primeira mais experiente, não inibem concluir que, em termos gerais: (1) a descentralização de fundos sectoriais ainda não é efectiva; (2) o envolvimento das instituições de planificação e consulta comunitária é efectivo; (3) o sistema de prestação de contas é complexo, moroso e contraproducente; (4) o sistema de monitoria e avaliação ao nível distrital pode ainda ser melhorado; (5) a capacidade de manutenção ao nível distrital precisa de fortalecimento; (6) há fraco envolvimento do sector privado na prestação de alguns serviços; (7) há desarticulação institucional na aplicação de alguma legislação; (8) os critérios de atribuição de fundos sectoriais são inconsistentes e pouco divulgados; e (9) há, nos distritos, falta de uma perspectiva multisectorial e sistemática de planificação. Face aos problemas identificados, este Relatório Final propõe algumas recomendações: nova abordagem sobre os fundos sectoriais, particularmente a sua integração nos PESOD; alinhamento dos instrumentos de planificação estratégicos locais com os nacionais; regulação em legislação própria dos critérios de alocação de fundos, capacitação institucional entre outras acções.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português; access to services / acesso a serviços; decentralization / descentralização; education / educação; infrastructure - roads / infrastructura - estradas

Muslims of northern Mozambique and the liberation movements - Bonate, Liazzat J. K. (Social Dynamics, 2009)
Despite the fact that the liberation war occurred in northern Mozambique, where a considerable number of Muslims lived, their contribution to the independence struggle has been little studied. This paper focusses on their participation in two nationalist liberation movements, Mozambican African National Union (MANU) and Frente de Libertação de Moçambique (FRELIMO), and demonstrates that the prevailing idea in scholarship about Muslims’ aloofness from the liberation struggle is unjustified. It argues that Muslim support and participation in the liberation movements stemmed primarily from grassroots African nationalism. Like most Africans, Muslims wished to end colonialism and recover their land from the Portuguese. African Muslims of northern Mozambique were well suited to support these movements, because Islam and chieftainship were linked to each other. Chiefs were believed to be the ‘owners’ and ‘stewards’ of the land, and a majority of Muslim leaders, whether traditional chiefs (régulos, in Portuguese) or Sufi leaders (tariqa khulafa’, in Arabic), were from the chiefly clans. Most importantly, Muslims of northern Mozambique had close historical and cultural ties to Tanganyika and Zanzibar, especially through Islamic and kinship networks. The involvement of Muslims in the liberation movements of those regions, in particular in Tanganyika African National Union (TANU), inspired and encouraged the Muslims of northern Mozambique to support MANU and FRELIMO, especially since these two movements were launched in Tanganyika and Zanzibar with TANU backing and the participation of Muslim immigrants from northern Mozambique.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

PARPA II – Relatório de Avaliação de Impacto Pesquisa Sobre o Combate À Corrupção - CS Advocacia, Consultoria e Serviços (Republica de Moçambique: Ministério da Planificação e Desenvolvimento, 2009)
Este estudo enquadra‐se no âmbito dos Mecanismos e Instrumentos de Monitoria e Avaliação do Plano de Acção para a Redução da Pobreza Absoluta 2006‐2009 (PARPA II), que preconizam a preparação de um Relatório de Avaliação de Impacto (RAI). O RAI tem como objectivo sintetizar informação sobre a pobreza e a evolução de indicadores socioeconómicos e analisar esta informação com uma visão particular para atribuir causa e efeito. Como parte das prioridades do PARPA II, o combate à corrupção é um dos temas a ser abordado no RAI. Neste âmbito, o presente estudo tem como objectivo geral, avaliar o impacto das medidas adoptadas no âmbito do combate à corrupção, com enfoque nos mecanismos de controlo interno (inspecções e auditorias), relacionando com a quantidade e qualidade dos recursos humanos existentes, o desempenho e impacto do Gabinete Central de Combate à Corrupção (GCCC).
Keywords: #Policy Document / Documento de Política; G - Mozambique / Moçambique; L - portuguese / português; corruption / corrupção; government policy / politica governamental

Country Review Report: Republic of Mozambique - African Peer Review Mechanism (African Peer Review Mechanism, 2009)
The report is divided into seven chapters. This introductory chapter is followed by Chapter Two, which provides an overview of Mozambique as a backdrop to the report. Chapters Three to Six evaluate developments and challenges in the four APRM focus areas (Democracy and Political Governance; Economic Governance and Management; Corporate Governance; and Socio-Economic Development) respectively. Each of these chapters has two sections: the first analyses the codes and standards of the APRM, while the second assesses the APRM‘s objectives for that thematic area. Each section begins with a summary of the CSAR, followed by the findings of the CRM and, finally, the APR Panel‘s recommendations on the identified challenges. Effort has also been made to highlight areas of best practice in boxes. Chapter Seven discusses the cross-cutting issues considered critical due to their wider impact on governance and thus require holistic, immediate and urgent attention. These salient issues are the following: Poverty and Inequality; Party/government/business dichotomy; Land; High levels of illiteracy; Eliminating aid dependency; Information flow and paucity of data; Inclusivity; Crime, safety and Security; Domestic violence; Capacity constraints and implementation challenge; Elections; and, Corruption. The Chapter also highlights three special issues of interest to Mozambique and the Mission - the Environment, land mines and Beira city. The NPOA received from Mozambique and the comments of the government are annexed to the report, as mandated by the APRM rules.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; governance / governação

Study on Community Land Rights in Niassa Province, Mozambique - Åkesson, Gunilla; Calengo, André; Tanner, Christopher (Swedish International Development Cooperation Agency (SIDA), 2009)
This report is based on information collected within the context of the study concerning Community Land Rights in Niassa Province in Mozambique, with special attention paid to the programme implemented by the Malonda Foundation. This programme is supported and financed by the Swedish Government and aims to promote private investment in the province while seeking, during the course of the process, to ensure equitable and beneficial social impact as an explicit objective, in particular for the local population.
Keywords: *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; employment / emprego; governance / governação; land governance / gestão de terra; youth / juventude

APRM Country Review Report Mozambique - República de Moçambique (República de Moçambique, 2009)
The major cross-cutting issues which featured prominently in all the thematic areas are highlighted below. A comprehensive approach is needed to address these issues as they have wider ramification for the various dimensions of governance in Mozambique. The following are the major thirteen crosscutting issues emerging from this report: Poverty and Inequality; Party/government/business dichotomy; HIV/AIDs; Land Ownership; High levels of illiteracy; High aid dependency; Information flow and paucity of data; Inclusivity; Crime, safety and Security; Domestic violence; Capacity constraints and implementation challenge; Elections; and, Corruption. CONCLUSION: The remarkable recovery that Mozambique has made since the end of the civil war in 1992 should make the people proud of their accomplishments. Over the last two decades, Mozambicans has made considerable progress in rebuilding its political, economic and social institutions, with noticeable progress. There is no doubt that Mozambicans can build on the successes highlighted in this report, while addressing the challenges in a vigorous manner, in order for the country to rapidly move forward. With its abundant natural resources, Mozambicans can exploit these resources for the benefit of the majority of its people. But this will be difficult to achieve without pragmatic and innovative solutions to the challenges arising from both the thematic and cross-cutting issues identified by this report.
Keywords: *non-public; G - Mozambique / Moçambique; L - english / inglês; conflict - civil war / conflito - guerra civil; governance / governação; health / saúde; natural resources / recursos naturais; poverty / pobreza

Moçambique: de uma economia de serviços a uma economia de renda - Brito, Luís de (IDeIAS, 2009)
A periodização que se segue tem como objectivo dar uma visão geral da evolução da economia moçambicana e situar a indústria no contexto desse desenvolvimento histórico. Uma das conclusões que se pode tirar desta visão panorâmica é que, mais de um século depois da partilha de África na Conferência de Berlim e de 35 anos de independência, a economia moçambicana apresenta ainda um padrão de tipo colonial, tendo como traço dominante a exportação de matérias-primas e recursos naturais.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; ⛔ No DOI found

Institutional Change and Community Based Natural Resource Management in Northern Mozambique - Anstey, Simon (University of Zimbabwe, 2009)
The objective of this study is to examine how the extensive institutional change of reforms to policy and legislation in Mozambique over the past decade has affected evolutions at the local level in the governance of natural resources. The particular focus of the research is an analysis of a community based natural resource management (CBNRM) initiative in North Sanga District of Niassa Province and a longitudinal study of its development between 1999 and 2007 based on my involvement as both field practioner and researcher. The research reveals institutional change in the governance of natural resources by communities in North Sanga as non-linear, non-equilibrium and scale interactive; as well as the agency in change being contingent on specific contexts (historical, social and environmental) and responsive to the beliefs of the actors involved. The importance of ‘crisis’ in promoting new cycles of adaptation for local governance is emphasised as is the significance of gaining formal ownership of the land by the community in acting as a key promoter of their agency in institutional and governance change.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; governance / governação; land governance / gestão de terra; natural resources / recursos naturais

Youth exclusion, violence, conflict and fragile states - Hilker, Lyndsay McLean; Fraser, Erika (Social Development Direct, 2009)
This report forms part of a portfolio of work on youth focussed on two interconnected thematic areas: youth, jobs and growth and on youth exclusion, fragile states and conflict and complements work being conducted to develop a Youth Participation Guide for DFID staff. It is intended to inform a DFID Policy Briefing and a practical Guidance Note on addressing youth exclusion and unemployment. The objectives of the study are: (i) To scope out existing evidence and analysis on the links between youth exclusion, violence, conflict and fragile states and distil this information to enable DFID (and partners) to better understand the implications for poverty elimination, state and community-building, peace-building, Disarmament, Demobilisation and Reintegration (DDR) and conflict prevention, in order to address the issues more effectively in policy and programmes; (ii) To develop a conceptual framework that renders this information manageable while still reflecting the many dimensions of this issue. The study involved a desk-based literature review and consultations with a small number of key informants from DFID, other donors, academia and youth groups. This study focuses mainly on people aged 15-24, but conceptualises “youth” as a transitional stage in life between childhood and adulthood rather than as a rigid construct based on age. It recognises the diversity of youth by gender, class, ethnicity and focuses on the multiple dimensions of exclusion that systematically disadvantage youth. It also takes a holistic approach to violence – recognising that in practice different forms of violence (e.g. political, criminal, interpersonal, extremism) may overlap and that some of the same structural and proximate factors may drive youth engagement in different forms of violence.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Social Protection in Mozambique: A new imperative? - Waterhouse, Dr Rachel; Lauriciano, Gil (IESE Conference ‘Poverty Dynamics and Patterns of Accumulation in Mozambique, 2009)
Even before the impact of a global economic crisis kicks in, there is renewed thinking in Mozambique about a wider role for the state in social protection. Proponents are still struggling to convince others of the economic and social value of a broader investment in social protection. This is against the backdrop of institutional resistance borne of Mozambique’s political and economic history. The government attitude to social protection has been influenced by colonial experience of an extractive rather than protective state and the legacy of post-Independence events and processes. After Independence in 1975, initial social service expansion was heavily undermined by war-time destruction and economic collapse in the 1980s. Post war, the Government’s top priorities were to re-establish security and rebuild infrastructure. However, political and economic liberalisation in the 1990s saw tight caps on state spending. Poverty was so widespread and deep that there seemed to be little scope for special consideration of the ‘poorest of the poor’... except for ad hoc initiatives, such as the food subsidy programme for the poor and unable to work. In the last 15 years, Mozambique has experienced impressive economic growth and poverty reduction. Nonetheless Mozambique continues to rank amongst the world’s poorest countries. Government is becoming more aware of chronic poverty and that large population groups are currently unable to escape the poverty trap. This raises debate about what can be done ... and promotes renewed thinking on social protection. There are still many obstacles to a coherent and comprehensive approach to social protection. These include: analytical limitations around the causes, consequences and extent of vulnerability as well as the potential social and economic benefits of social protection; institutional barriers; budgetary limitations; and perceived political risk. However, there is also a growing acceptance of the relevance and importance of social protection to reduce vulnerability, build resilience and contribute to poverty reduction. These issues need to be addressed at policy and practical level, if Mozambique is to effectively address the growing challenge of chronic poverty.
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - english / inglês; poverty / pobreza; social protection / proteção social

The group effect: Social cohesion and health outcomes - Bruhn, John (Springer New York, NY, 2009)
Sociologists and anthropologists have had a long interest in studying the ways in which cultures shaped different patterns of health, disease, and mortality. Social scientists have documented low rates of chronic disease and disability in non-Western societies and have suggested that social stability, cultural homogeneity and social cohesion may play a part in explaining these low rates. On the other hand, in studies of Western societies, social scientists have found that disease and mortality assume different patterns among various ethnic, cultural and social-economic groups. The role of stress, social change and a low degree of cohesion have been suggested, along with other factors as contributing to the variable rates among different social groups. Social cohesion has been implicated in the cause and recovery from both physical and psychological illnesses. Although there has been a large amount of work established the beneficial effects of cohesion on health and well-being, relatively little work has focused on HOW increased social cohesion sustains or improves health. This work is based on the premise that there are risk factors, including social cohesion that regulate health and disease in groups. One of the challenges is how to measure social cohesion - it can be readily observed and experienced but difficult to quantify. A better understanding of how social cohesion works will be valuable to improving group-level interventions. © Springer Science+Business Media, LLC 2009. All rights reserved.
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; health / saúde

Doing Business with the Ladies: Gender, Legal Reform, and Entrepreneurship in the International Finance Corporation - Bedford, Kate (Labour, Capital and Society / Travail, capital et société, 2009)
Since 2007 the World Bank's gender approach has moved away from the Wolfensohn-era emphasis on gender as central to social development concerns, towards a business case model that involves a far greater role for the private sector in efforts to reduce poverty and achieve gender equity. Using a case study of the International Finance Corporation (IFC) and its project, 'Doing Business', to promote the ease of doing business across the world, I ask what this new direction entails for the Bank's gender and development efforts, and examine the new links being forged between gender empowerment and free market reform. The article focuses on three themes in this regard: first, how attention to gender within the 'Doing Business' project helps promote labour market deregulation; second, the contested way in which free markets, legal reform, and gender equality are linked together; and third, the regional reconfigurations of Gender and Development (GAD) evident in the project's report on Women in Africa, wherein women entrepreneurs are celebrated and new networb of GAD specialists are drawn together.
Keywords: *indexed; *tagged; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; entrepreneurship / empreendedorismo; gender / género; law / direito; ⛔ No DOI found

Jovens e associações em Moçambique: motivações e dinâmicas actuais [Youths and associations in Mozambique: motivations and current dynamics] - Biza, Adriano Mateus (Saúde e Sociedade, 2009)
O presente artigo é uma reflexão sobre dinâmicas associativas de jovens no Moçambique pós colonial. O objectivo desta reflexão foi identificar e analisar as motivações de engajamento dos jovens nesses agrupamentos. Baseando-se em aproximações empíricas feitas a duas associações de jovens - Associação Aro Juvenil e Associação Positiva Juvenil - a análise demonstra que dinamica associativa de jovens mete em evidência relações complexas entre identidade, contexto, o privado, o público e o afectivo. Embora haja múltiplas motivações, a adesão dos jovens em associações associa trajectórias e expectativas individualizadas. A nível discursivo, a entrada na vida associativa representa uma forma de legitimação sóciopolítica em resposta a um discurso que considera os jovens passivos e pouco intervenientes na solução dos problemas que lhes afecta em particular e à sociedade no geral. A nível das práticas associativas quotidianas, os jovens reintrepretam e dão outro sentido às motivações do seu engajamento: para lá dos objectivos formais, pretensamente desenvolvimentistas, altruistas e humanitários, o associativismo é uma estratégia de vida e de realização de projectos individuais. Criar uma associação e/ou nela aderir pode significar maiores possibilidades de aceder e controlar recursos e capitais diversificados como emprego/profissão, dinheiro, trabalho, poder, reconhecimento e prestigio, formações entre outros que de outra forma não seria possível. en: This article reflects on youth associations dynamics in Postcolonial Mozambique. The aim is to identify and analyze motivations for young people's involvement in such groups. Based on empirical work with two youth associations - namely "Associação Aro Juvenil" and "Associação Positiva Juvenil" - the assessment finds that youth associations dynamics highlights intricate relationships involving identity, context, private, public and affective milieus. Although there are multiple motivations, young people's adherence to associations is combined with individual life stories and expectations. At the discourse level, entrance to the associative life represents a form of socio-political legitimation in response to other narratives that consider young people very passive and less intervening in finding solutions to their own problems, and society's in general. At the level of day-to-day practices, young people re-interpret and give a different sense to their motivations and commitment: beyond formal objectives - arguably development-oriented, altruistic and humanistic - associations are a life strategy for the accomplishment of individual achievements. To create an association and/or take part in one may imply greater possibilities of accessing and controlling diversified resources and capitals, such as a job/occupation, money, work, power, recognition, prestige, and training, among others, which would be otherwise impossible.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; citizenship & participation / cidadania e participação; decentralization / descentralização; youth / juventude

The politics of gradualismo: popular participation and decentralised governance in Mozambique - Buur, Lars (Rethinking Popular Representation., 2009)
The question of how to proceed with democratic decentralisation has been of political concern in Mozambique over the past decade. In accordance with post-war constitutional commitments to démocratisation after the country’s post-independence flirtation with socialism and a high degree of centralism, the process of decentralisation has taken two forms. First, a system of locally elected governments in the form of municipalities (municipios) for the urban and semi-urban areas was approved in 1997 to cover the devolution of direct although limited powers and functions to autonomous elected bodies. The Municipal Law (2/1997) made provision for locally elected municipalities (autarquias locais) in 33 urban or peri-urban settings.1 Second, for the rest of the population (roughly .70 percent) and the local state administration, the process of decentralisation has taken the general form of de-concentration and a transfer of responsibility to lower level bodies within the state sector combined with different forms of participatory mechanisms for representation and consultation. These participatory mechanisms are grounded in community- based organisations claiming representative status on the basis of identity, interest, community, and similar factors.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização; governance / governação

Programas de saúde materno-infantil em Moçambique: marcos evolutivos e a inserção da enfermagem (Programs of maternal and infant health in Mozambique: gradual landmarks and the insertion of nursing) - Lourenço, Maria Acácia Ernesto; Tyrrell, Maria Antonieta Rubio (Escola Anna Nery, 2009)
See english abstract below. Pesquisa centrada nas políticas públicas do governo moçambicano para o setor da saúde, com foco voltado para programas de assistência à saúde materno-infantil. Tem o propósito de apresentar contextos básicos para a reflexão sobre a filosofia da implantação e implementação dos programas e a inserção da Enfermagem, mostrando seus marcos evolutivos. Constatou-se que, na década 70, o Sistema Nacional de Saúde adotou o Programa de Proteção Materno-Infantil, que na década de 80 ficou concebido como Programa de Saúde Materno-Infantil e, posteriormente, na década 90, ficou inserido no Programa Nacional Integrado de Saúde Materno-Infantil e Planejamento Familiar, Programa Alargado de Vacinação, Saúde Escolar e do Adolescente, incluindo Saúde Sexual e Reprodutiva. A inserção da Enfermagem foi evidenciada na implementação das ações assistenciais. Os marcos evolutivos foram: a introdução dos cursos específicos de Enfermagem em saúde materno-infantil do nível básico ao superior e abrangência dos serviços do Programa Nacional Integrado. ABSTRACT For the interest to know about the public Policies of Mozambican government to the Health sector, this research put much emphasis on the process of implantation and implementation of assistance programs to maternal health looking at reflection about the philosophy of including nursing through ever-changing world or marked changes. Established in the 1970s, the National Health System came up with a maternal health protection program which in the 1980s was drawn into Maternal Health Program. This, in the 1990s was included in the National integrated program of maternal health and family planning, integrating a broad vaccination program, school health and adolescent sexual reproductive health. The inclusion of nursing in the implementation of integrated program became as the evidence through action assistances. The evolutional signs were the introduction of specific courses of Maternal and Infant Health Nursing from basic to superior levels, including the service of National Integrated Program.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - portuguese / português; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; youth / juventude

Gender and Poverty in Northern Mozambique - Tvedten, Inge; Paulo, Margarida; Tuominen, Minna (Chr. Michelsen Institute, 2009)
The main objective of this report is to capture the local configurations of gender relations in Nampula, by focussing on one rural and one urban area in the province. The former is the coastal and rural district of Mossuril, which is considered one of the most deprived districts in the province, both in terms of material poverty and human development (MAE 2005). The urban areas are Muatala and Namutequeliua, which are two of the most populous bairros in the city of Nampula and largely inhabited by migrants from the coast and hence share historical and sociocultural roots with Mossuril.
Keywords: *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mossuril; GP - Nampula; Health PEA; L - english / inglês; education / educação; employment / emprego; gender / género; health / saúde; poverty / pobreza

Monitoring and Evaluating Mozambique’s Poverty Reduction Strategy PARPA 2006-2008. A Synopsis of Three Qualitative Studies on Rural and Urban Poverty. - Tvedten, Inge; Rosário, Carmeliza; Paulo, Margarida (Chr. Michelsen Institute, 2009)
The purpose of this synopsis is to facilitate discussions between the government, civil society organisations, donors and other stakeholders in Mozambique’s efforts to reduce poverty and, more specifically, to contribute to the Impact Assessment Report (Relatótio de Avaliação de Impacto, RAI) which is to be carried out in 2009. We will focus on our main findings and preliminary conclusions, and will to the extent possible avoid repeating data found in the original reports to ease accessibility. The discussions related the synopsis will also be used to further identify the most relevant topics and approaches for the final three studies, in order to secure their maximum utility for the government’s monitoring and evaluation programme. The synopsis will be divided into six parts following this Introduction. In Chapter 2 we briefly account for the analytical framework and methodological approaches of the studies. In Chapter 3 we present what we have identified as aspects of Mozambique’s political economy with particular impacts on the situation in local communities. In Chapter 4 we analyse the main features of the political context at the level of districts through which poverty reduction is implemented. In Chapter 5 we present the main findings from the adapted surveys we have carried out, with a focus on the similarities and differences between the three areas of study. In Chapter 6 we assess the outcome of our qualitative and participatory approaches to our analyses. And finally, in Chapter 7, we present preliminary conclusions and recommendations from the first three studies and outline the approach of the three follow-up studies.
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - evaluation / avaliação; poverty / pobreza; urbanization / urbanização

Power and Participation in Rural Development: A Case Study from Mozambique - Valderrama, Camilo Eduardo (Institute of Development Studies, University of Sussex, 2009)
This study on power and participation in post-conflict settings analyzes a rural development project in Mandimba District of Northern Mozambique. The purpose is to gain understanding of the dynamics and possibilities of participatory approaches for increasing the influence of previously excluded actors in decision-making processes. The methodology for this study reflects two broad yet intertwined approaches. For the first component, the Mozambique in-depth case study research, I draw on my role as a participant observer as well as other more traditional field research approaches. A variety of qualitative methods were used for the collection of the information, including review of documentary sources, participant observation, key informant and focus group interviews. The initial data collection lasted about eight months in different phases between 1998 and 1999. In Mozambique, but also in subsequent years, my approach drew upon principles of reflective practice, where I learned not only through the study of others, but through reflections on my work as a practitioner in conflict areas being studied. This latter approach was particularly important when triangulating and extending the findings from the Mozambique study to other war-torn settings in which I later worked in Kosovo, Pakistan and Chad and when reviewing documented experiences in participatory processes in Afghanistan and East Timor. A 'power over' and 'actor oriented' approach informed data collection and analysis of the information. The findings show that inclusive participatory approaches may fail if they do not address power. They may sideline power asymmetries and fail to set rules of involvement for actors within the project. In addition, structural and functional factors related to the project frame can enhance or constrain participation. The finding also shows that the inflexibility of the project frame constrains actor engagement in decision-making processes. The theoretical implication of this research calls for an approach to power rooted in the mix of conflict and consensual understanding of power. Practical implications point towards a greater emphasis on 'decision ruling', i.e. setting the 'rules of the game' for decision-making in participatory processes.
Keywords: *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mandimba; GP - Niassa; L - english / inglês; citizenship & participation / cidadania e participação; conflict - civil war / conflito - guerra civil; conflict / conflito; power / poder; rural development / desenvolvimento rural

Contexto Politico e institucional da protecao social em Mocambique - Waterhouse, Rachel; Lauriciano, Gil (Protecção Social: Abordagens, Desafios e Experiências para Moçambique, 2009)
Mesmo antes de se fazer sentir o impacto duma crise económica global, há um pensamento renovado em Moçambique sobre um papel mais amplo do Estado na protecção social. Os proponentes lutam de modo a convencer os outros do valor económico e social dum investimento mais alargado na protecção social. Isto vai contra o pano de fundo da resistência institucional, que a história política e económica de Moçambique acarreta. Moçambique já era unido como uma nação sob o regime colonial português, desde o princípio do século XX. O governo colonial praticou um regime altamente extractivo, fornecendo pouco para o bem-estar social ou a para a protecção social. Um breve período de políticas marxistas-leninistas após a independência nacional em 1975 –quando o governo da Frelimo tentou ampliar os serviços sociais básicos em todo o país– foi rapidamente superado pelo colapso económico e pela guerra, seguido por um rígido exercício de poder pelo estado sob ajustamento estrutural. Um pensamento renovado coerente e abrangente sobre um papel mais amplo do Estado no fornecimento duma Protecção social dos seus cidadãos é ainda emergente e controverso. Este artigo apresenta uma breve panorâmica do contexto político e institucional em que este debate está a ganhar importância.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; social protection / proteção social